ANALISIS HUBUNGAN FAKTOR EKSOGEN DAN ENDOGEN TERHADAP KEJADIAN DERMATITIS AKIBAT KERJA PADA PEKERJA PENYAMAKAN KULIT PT. ADI SATRIA ABADI PIYUNGAN, BANTUL - Rahma, Gresi Amarita; Setyaningsih, Yuliani; Jayanti, Siswi (Jurnal Kesehatan Masyarakat (e-Journal), 2017)
Occupational dermatitis is skin disorders caused by contact with certain substances in the workplace. There are exogenous factors and endogenous factors which affects occupational dermatitis. PT. Adi Satria Abadi is an industry of leather tanning that requires dozens of chemicals in every process. This research aims to analyze the relationship of exogenous factors (working period, number of chemical type, mechanical factors) and endogenous factors (age, personal hygiene, personal protective equipment) with occupational dermatitis at PT. Adi Satria Abadi. The research is conducted analytically with cross sectional approach and explanatory research. The sample involved in this research is total population of wet production are 48 workers. The independent variable data was collected by questionnaire by respondent and occupational dermatitis data based on doctor medical check up. According to the result of research using Chi-Square test showed that the related variables with occupational dermatitis were number of chemical type (p-value = 0,001), mechanical factors (p-value = 0,001), personal hygiene (p-value = 0,001), and the type of work section (p-value = 0,001). While unrelated variables with occupational dermatitis were working period, age, and personal protective equipment.